How do self-efficacy and career development affect employees' work at PT Telkom Indonesia Palangka Raya? - Yuandi, Muhammad Abdi; Tindan, Tindan; Peridawaty, Peridawaty (JSM: Jurnal Sains Manajemen, 2024)
This study aims to examine the impact of self-efficacy and career development on the performance of employees at PT. Telkom Indonesia Palangka Raya Branch. The sample will be determined using the saturation sampling technique, including all 70 PT employees. Telkom Indonesia Palangka Raya Branch as respondents. The research methodology employs a causal associative research design, utilizing a quantitative method—techniques for collecting data through questionnaires. The data were examined using descriptive and multiple linear analyses utilizing the SPSS program version 22. The findings indicated that both self-efficacy and career development had a concurrent and partial impact on the performance of PT. Telkom Indonesia Palangka Raya Branch